Demographic Profile and Outcome of Mechanically Ventilated Children in a Tertiary Care Hospital of a Developing Country - Sahoo, Bandya; Jain, Mukesh Kumar; Thakur, Bhaskar; Mishra, Reshmi; Patnaik, Sibabratta (Journal of Nepal Paediatric Society, 2018)
Introduction: The need for mechanical ventilation (MV) is an absolute indication for admission to Paediatric intensive care unit (PICU). Management of children requiring invasive ventilation in resource limited developing countries is challenging. Scare data is available from Asian countries regarding use of MV in PICUs. The objectives of this study were to determine the clinical profile, characteristics, common causes for ventilation, ventilation related complications and final outcome of these patients. Material and Methods: A retrospective study of children requiring ventilator support in PICU of Kalinga Institute of Medical Sciences from January 2014 to December 2016 was done. Data collected included epidemiological trends, indications for ventilation, complications, length of stay on ventilator and outcome. Results: A total of 1172 patients were admitted to PICU, 101 (8.6%) patients required MV. 42% of the mechanically ventilated patients were infants and 75% were males. Impending respiratory failure (34.6%) and low Glasgow coma scale (17.8%) were the commonest indication for ventilation in this study. The median length of MV was 2.1 days. The mortality rate of these children was 38.6%. We report the epidemiological trends, frequency, indications and outcomes of children requiring ventilator support in PICU. Analysis of this data can be helpful in improving outcome in future by planning better treatment strategies. Conclusion: The frequency of MV in our PICU is low. Respiratory failure was the most common reason for mechanical ventilation.